EXPLORING STUDENT TEACHERS' ANXIETY RELATED TO THE TEACHING PRACTICUM: A Case Study in One Junior High School in Bandung - Lestari, Hikmah (2017)
This study aims to explore the anxiety that the student teachers encountered during the teaching practicum, especially the student teachers from Indonesia University of Education. This study belongs to a case study in one junior high school in Bandung. There were three student teachers participated in this research. They did the teaching practicum from February to June 2016. Semi-structured interviews and diaries which the student teachers kept during the teaching practicum were analyzed to investigate the sources that contribute to their anxiety as well as the strategies to overcome their anxiety. Key words: anxiety, student teachers, teaching practicum Penelitian ini bertujuan untuk menginvestigasi kecemasan yang dialami oleh guru praktikan selama masa PPL (Program Praktik Lapangan), khususnya guru praktikan yang berasal dari Universitas Pendidikan Indonesia. Penelitian ini merupakan studi kasus di salah satu sekolah menengah pertama di Bandung. Ada tiga guru praktikan yang menjadi subjek dalam penelitian ini. Wawancara semi struktural dan jurnal harian yang dimiliki oleh guru praktikan selama PPL dianalisis untuk menemukan sumber kecemasan dan strategi untuk mengatasi kecemasan yang mereka alami selama PPL. Kata kunci: kecemasan, guru praktikan, PPL